Analisis Tingkat Kepuasan UMKM Terhadap Penerapan Digital Payment Qris Pada Pelaku UMKM Bali Bangkit Di Kota Denpasar - Kusumawati, Ni Putu Diah; Putra, I Made Endra Lesmana (UNHI Press, 2025)
The research aims to determine the level of satisfaction of MSMEs with the implementation of Qris digital payments among Bali Bangkit MSMEs in Denpasar City. Data collection use a preliminary survey method and distributing questionnaires to Bali Bangkit MSME owners in Denpasar City. The population in this research is all small and medium industries in Bali Bangkit Denpasar with a total of 72 Bali Bangkit MSMEs in Denpasar City. The sample was determined using a census technique where all members of the population were sampled so that the sample in this study were 72 Bali Bangkit MSMEs in Denpasar City. Data analysis was carried out by comparing the perception of user expectations with the performance of Qris digital payments as perceived by Bali Bangkit MSMEs in Denpasar City. Based on the results of the analysis, the conclusion of this research is that the user satisfaction index is 96.47%, which shows that the user satisfaction index is in the very satisfied criteria. Overall, users can be said to be very satisfied with using Qris.